The Relationship of Sedentary Behavior and Sleep Duration to The Incidence of Obesity in Children under Five in Central Jakarta and The Review of Islamic Perspective - Anisya Fitriah; Diniwati Mukhtar; Qomariyah Sachrowardi; Endy Muhammad Istiwara (Junior Medical Journal, 2023)
Introduction: Children under five should have their nutritional status checked regularly due to their susceptibility to diseases and nutritional problems. Inappropriate or excessive accumulation of fat, called obesity, can jeopardize their health. Assessment of nutritional status in obese toddlers can use anthropometric standards that are converted into Z-score values based on IMT/U with the category of obesity if the Z-score value is +3 SD. Sedentary behaviour is when a person spends sitting or lying down with low energy expenditure outside sleep. Children and adolescents with high sedentary behaviour are prone to an increase in adipocytes that cause obesity. Children aged 3-5 years with poor sleep duration (10 hours/day) are at greater risk of obesity. Methods: This type of research is quantitative with a cross-sectional design. The sample of this study was 70 children aged 2-5 years in Sawah Besar District, who were included in the inclusion criteria. Results: Out of 70 toddlers in Central Jakarta, 37 people (52.9%) were obese, and 33 (47.1%) were ordinary. Based on the results of statistical tests using the Chi-Square test, the p-value is 0.05, which can be concluded that there is a relationship between sedentary behaviour and obesity and a relationship between sleep duration and obesity. Conclusion: The research results show a significant relationship (p 0.03) between sedentary behaviour and obesity, with an Odd Ratio value of 3.137. There is also a meaningful relationship (p 0.016) between sleep duration and obesity, with an Odd Ratio value of 3.646 in Sawah Besar District, Central Jakarta toddlers.